Development of Bahasa Indonesia for Foreign Speaker’s Learning Material Based on Indonesian Cultures-Literatures and 5C Integrated - Purbarani, Etsa; Muliastuti, Liliana (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2023)
Currently, BIPA learning material which includes grammar, language skills and culture is delivered in an integrative manner, but the learning activities in it have not fully provided a way for foreign students to be able to communicate in Indonesian properly. The appropriateness of this communication can be achieved based on the context, society and culture of Indonesia. Because of this gap, BIPA students will experience communication barriers because there are differences between the Indonesian language learned in the classroom and the use of Indonesian in society. Apart from that, cross-cultural understanding has not been well established because the use of cultural and literary topics as language arts which can be an effective means of improving mastery of Indonesian language skills is not yet optimal. Based on this situation, this research focuses on developing a BIPA teaching material model based on Indonesian culture and literature by integrating the 5C aspects, namely communication, culture, connections, comparison, and communities. By integrating these five aspects in teaching materials for listening, speaking, reading, writing and grammar, foreign students can master Indonesian language competencies better and more comprehensively. These five aspects are covered in topics and discussions using various topics related to Indonesian culture and literature. The teaching material model developed will focus on the advanced level or BIPA 7.